2010
DOI: 10.1016/j.aquatox.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exposure to petroleum hydrocarbons upon cardio-respiratory function in the common sole (Solea solea)

Abstract: The long term consequences of oil exposure upon marine populations are still poorly evaluated. One particular missing piece of information relates to the link between oil exposure, individuals' ability to face environmental contingencies and populations' production and dynamics. In that context, the present paper investigates the impact of oil exposure upon fish cardio-respiratory performance, this performance being viewed as a key determinant of individual fitness. Experimental conditions replicated the conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…It was hypothesized that the relative failure of the cohort present in the nursery ground at the time of the Erika oil spill was linked to this impaired ability for environmental adaptation (Claireaux and Davoodi 2010;Davoodi and Claireaux 2007). This study strengthened this view.…”
Section: Consequences For the Recruitmentsupporting
confidence: 76%
“…It was hypothesized that the relative failure of the cohort present in the nursery ground at the time of the Erika oil spill was linked to this impaired ability for environmental adaptation (Claireaux and Davoodi 2010;Davoodi and Claireaux 2007). This study strengthened this view.…”
Section: Consequences For the Recruitmentsupporting
confidence: 76%
“…The ultimate results are hypoxia, coma, and even death. The experimental results of Claireaux and Davoodi (2010) shown that the cardio-respiratory responses of fish (Solea solea) were depressed under oil exposure and were unable to meet the temperature-driven increase in tissues oxygen demand. This finding profoundly indicated that the coastal copepod community encounters extra challenge in oil-contaminated waters under seawater temperature elevation caused by global warming.…”
Section: Discussionmentioning
confidence: 99%
“…The question is whether these adverse functional effects are limited to developmental exposures. Impaired cardiorespiratory function has been observed following acute petroleum hydrocarbon exposure in adult common sole (Claireaux and Davoodi, 2010). The cardiovascular system is intimately associated with other physiological parameters essential for survival, including metabolic rate and aerobic capacity (Farrell, 1996(Farrell, , 2002Claireaux et al, 2006) and negative PAH effects could impact fitness.…”
Section: Introductionmentioning
confidence: 98%